The impact of alternative childcare policies on mothers' employment in selected EU countries - Edlira Narazani; Ana Agúndez García; Michael Christl; Francesco Figari (Global Labor Organization (GLO), 2023)
This paper contributes to the debate on the revision of the Barcelona targets on childcare, as promoted by the European Commission in 2022, that aims to provide childcare for children below the age of 3. Using EUROLAB, a structural model of labour supply that can also accounts for labour demand constraints, we estimate female labour market participation reactions to alternative scenarios of formal childcare policies in European countries with very low child care provision for children below 3. We quantify the potential increases in the labour supply of mothers (at the extensive and intensive margins) in the case of fulfilling potential new targets of childcare provision (40%, 50%, 60% and 65%). Achieving these targets would lead to significantly increased labour supply of mothers especially in countries like Hungary and Poland where the current share of formal childcare and/or female labour participation is low. In countries like Portugal, that are far beyond the existing childcare target, changes in labour supply incentives are instead expected to be moderate. We further show that when accounting for labour demand, the expected final employment effects will be less pronounced, but still positive.
Keywords: J20; J22; J23; J13; 330; Labour market equilibrium; labour supply; labour demand; structural models; discrete choice; childcare